Governing Peace: Global Rationalities of Security and UNESCO’s Culture of Peace Campaign - Ilcan, Suzan; Phillips, Lynne (Anthropologica, 2022)
This essay interrogates the relationship between governance and peace, and explores how campaigns for peace are being developed on global scales. We analyze how UNESCO’s Culture of Peace program governs peace through "global rationalities of security." These rationalities—embodied in programs of action, training and capacity-building schemesand information-sharing practices—are geared towards investing in people in ways that individualize them and govern their conduct in the future. Campaigns for "a culture of peace" attempt to make particular individuals and groups responsible for acquiring certain kinds of values of "peace" and "security." In light of the current wars, violence and conflicts that besiege lives and livelihoods, the processes of governing peace force us both to question the contradictions that inhabit global peace efforts and to offer alternative thinking about peace.